Klasifikasi Citra Bekicot Menggunakan Algoritma Support Vector Machine - Peryanto, Ari; Hakim, Lukmanul; Nugrahantoro, Achmad (Jurnal IT UHB, 2025)
Snails are one of the animals that are widely found in Indonesia, but they are often considered pests and are not used optimally. In fact, there are several types of snails that have high economic value and can be exported, especially to countries such as France that use snails as restaurant cuisine. On a small scale, the process of classifying local and imported snails can be done manually however, if there are a lot of them, an automated system is needed to help the classification process become faster and more accurate. This study proposes a classification method based on Support Vector Machine (SVM) to distinguish local and imported snails. SVM is used as a classification model because of its ability to handle high-dimensional data and complex patterns. The results of the study showed an accuracy of 54%, so it can be an effective solution in the process of sorting snails on a large scale.